Are risk preferences dynamic? Within-subject variation in risk-taking as a function of background music - Marja Liisa Halko; Markku Kaustia (Goethe University Frankfurt, Center for Financial Studies (CFS), 2012)
This paper investigates whether preference interactions can explain why risk preferences change over time and across contexts. We conduct an experiment in which subjects accept or reject gambles involving real money gains and losses. We introduce within-subject variation by alternating subjectively liked music and disliked music in the background. We find that favourite music increases risk-taking, and disliked music suppresses risk-taking, compared to a baseline of no music. Several theories in psychology propose mechanisms by which mood affects risktaking, but none of them fully explain our results. The results are, however, consistent with preference complementarities that extend to risk preference.
urn:nbn:de:hebis:30:3-272526
Keywords: D81; G11; 330; Risk Taking; Music; Preference Interaction; Risikopräferenz; Musik; Nutzen; Test